Insight into genetic susceptibility to male breast cancer by multigene panel testing: Results from a multicenter study in Italy. Issue 2 (24th January 2019) - Rizzolo, Piera; Zelli, Veronica; Silvestri, Valentina; Valentini, Virginia; Zanna, Ines; Bianchi, Simonetta; Masala, Giovanna; Spinelli, Alessandro Mauro; Tibiletti, Maria Grazia; Russo, Antonio; Varesco, Liliana; Giannini, Giuseppe; et al.
Abstract : Breast cancer (BC) in men is rare and genetic predisposition is likely to play a relevant role in its etiology. Inherited mutations in BRCA1/2 account for about 13% of all cases and additional genes that may contribute to the missing heritability need to be investigated. In our study, a well‐characterized series of 523 male BC (MBC) patients from the Italian multicenter study on MBC, enriched for non‐ BRCA1/2 MBC cases, was screened by a multigene custom panel of 50 cancer‐associated genes. The main clinical‐pathologic characteristics of MBC in pathogenic variant carriers and non‐carriers were also compared. BRCA1/2 pathogenic variants were detected in twenty patients, thus, a total of 503 non‐ BRCA1/2 MBC patients were examined in our study. Twenty‐seven of the non‐ BRCA1/2 MBC patients were carriers of germline pathogenic variants in other genes, including two APC p.Ile1307Lys variant carriers and one MUTYH biallelic variant carrier. PALB2 was the most frequently altered gene (1.2%) and PALB2 pathogenic variants were significantly associated with high risk of MBC. Non‐ BRCA1/2 pathogenic variant carriers were more likely to have personal ( p = 0.0005) and family ( p = 0.007) history of cancer. Results of our study support a central role of PALB2 in MBC susceptibility and show a low impact of CHEK2 on MBC predisposition in the Italian population. Overall, our data indicate that a multigene testing approach may benefit from appropriately selected patients with implications for clinical management and counseling of MBC patients and their family members. Abstract : What's new? While multigene panel testing for breast cancer predisposition has been performed extensively in females, its use in male breast cancer (MBC) patients has been much more limited, despite a likely role for genetic predisposition in MBC. In this multicenter study in Italy, panel testing involving 50 cancer‐associated genes identified germline pathogenic variants in about 5 percent of BRCA1/2 ‐negative MBC patients. In non‐ BRCA1/2 MBC, the most frequently mutated genes were PALB2 and ATM, with PALB2 mutations having a major impact on MBC risk. By comparison, mutations in CHEK2 had little impact on MBC predisposition in the Italian population.